An investigation of the degradation of ceramic coatings on metals using a microwave technique - Owston, C. N. (College of Aeronautics)
Metal components for use in high temperature oxidising or corrosive environments often require protection. Many of the coatings used are complex but the two basic types are as shown in figure 1. In type A, source material is diffused into the surface of the component. When heated in air some of the source material oxidises to form a thin protective ceramic layer. The coating continues to be protective as long as there is an adequate supply of source material to provide new ceramic to replace any lost from the surface. Any non-destructive testing system for such a coating must give information on the amount of source material in reserve. In system B (figure 1) the relatively thick ceramic coating is applied as a slurry or is sprayed on by flame or plasma arc. The ceramic gives erosion corrosion and thermal protection. Owing to the porosity of the ceramic oxidation/corrosion of the protected metal will eventually take place. This attack is the preliminary stage t- separation of the ceramic from the metal and also to failure of the metal component. Non-destructive testing, must give information on the interfacial region between ceramic and metal.